Pengaruh Sistem Informasi Akuntansi, Sumber Daya Manusia dan Siklus Hidup Perusahaan terhadap Kualitas Laporan Keuangan - Sastra, Heiko; Hardinto, Andi Aditya (UNIVERSITAS KALBIS, 2025)
This study aims to analyze the influence of accounting information systems, human resources, and the corporate life cycle on the quality of financial statements in hospitality companies in the Greater Jakarta area (Jabodetabek). The research uses a quantitative approach with data collected through questionnaires distributed to financial managers or supervisors. The sample size was determined based on Hair et al.'s guidelines, and data were analyzed using multiple linear regression. The results show that the accounting information system affects the quality of financial statements, while human resources and the corporate life cycle do not. However, collectively, the three variables still have an influence on the quality of financial statements.